Shear induced carboplatin binding within the cavity of a phospholipid mimic for increased anticancer efficacy - Mo, J.; Eggers, P.; Chen, X.; Ahamed, M.; Becker, Thomas; Lim, L.; Raston, C. (Nature Publishing Group, 2015)
Vesicles 107 ± 19 nm in diameter, based on the self-assembly of tetra-para-phosphonomethyl calix[4]-arene bearing n-hexyl moieties attached to the phenolic oxygen centres, are effective in binding carboplatin within the cavity of the macrocycle under shear induced within a dynamic thin film in a continuous flow vortex fluidic device. Post shearing the vesicles maintain similar diameters and retain carboplatin within the cavity of the calixarene in a hierarchical structure, with their size and morphology investigated using DLS, TEM, SEM and AFM. Location of the carboplatin was confirmed using NMR, FTIR, ESI-MS and EFTEM, with molecular modelling favouring the polar groups of carboplatin hydrogen bonded to phosphonic acid moieties and the four member cyclobutane ring directed into the cavity of the calixarene. The loading efficiency and release profile of carboplatin was investigated using LC-TOF/MS, with the high loading of the drug achieved under shear and preferential released at pH 5.5, offering scope for anti-cancer drug delivery. The hierarchical structured vesicles increase the efficacy of carboplatin by 4.5 fold on ovarian cancer cells, lowered the IC50 concentration by 10 fold, and markedly increased the percent of cells in the S-phase (DNA replication) of the cell cycle.